Demystifying Educational Robotics with FOCORE: from Very Low Cost Software and Hardware Technologies to the Development of New Methodologies and Curriculum for Continuing Teacher Education and Teaching of Brazilian Basic Education Students - Fernandes, Carla; S. Júnior, Orivaldo; Oliveira, Denilton; Garcia, Luciane; Burlamaqui, Aquiles; Melo, Julio; Sá, Sarah; Soares, Allyson; Souza, Anderson; Barrios-Aranibar, Dennis; Patiño-Escarcina, Raquel; Fabro, João; et al. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
This article is of informative proposal about the first research network with Latin American scope in the area of Robotics in Education (RE). We came up with a heterogeneous and multidisciplinary group, with the participation of universities and federal institutes in Brazil and a Peruvian university. The network aims to Study and Develop Methodologies for Implementing Educational Robotics in Public Education Systems. The proposal emphasizes the analysis of policies and experiences in the Continuing Education of Teachers as well as the development and improvement of software, hardware, curricula, and teaching methodologies in the Robotics in Education area. During the manuscript, some of the state of the art is given on public policies aiming the use of Educational Robotics in the Brazilian education scenario, with a critical reﬂection on the contributions of RE, either as an active methodology for different purposes or in the teachinglearning process in public schools. Next, based on the initial study, we will be showing developed and improved tools for RE, including software and hardware. Our studies also seek the scientific foundations to propose improvements in curricula and course proposals for continuing education and learning of RE in schools.